Parental Knowledge of Malnutrition as a Cause of Infant and Child Mortality Rate in Torbu Community, Sierra Leone - Tommy, Alieu; Musa, Taha Hussein; Kawuk, Joseph; Ghimire, Upama; Obore, Nathan; Papabathini, Shireen Salome; Fornah, Lovel (International Journal of Child Health and Nutrition, 2020)
Malnutrition is a significant public health problem over the world, with severe impact in developing countries, including Asia and Africa. This paper present to assess malnutrition as a cause of infant and child mortality rate in Torbu community in Bo city, Sierra Leone. We used a community-based cross-sectional survey. A total of 80 mothers with children of under five years were selected using convenience sampling from the different divisions of Bo city. The findings showed that 48 (60%) of the respondents have never been sensitized nor have any knowledge about Malnutrition, of which 16 (50%) were informed via radio while 50 (63%) were not aware of any nutrition facility around the community. Besides, 56 (70%) of the respondents did not practice exclusive breastfeeding, 64 (80%) fed their children on only carbohydrates mainly in the form of rice, and 26 (32.5%) had one meal per day. 64 (80%) reported their children to have been admitted due to malnutrition (with mainly protein-energy malnutrition), while over a half 46 (57%) reported having lost a child to malnutrition. Thus, we recommended more nutrition education to address the poor Infant and Young Child Feeding (IYCF) practices as well as targeted health interventions to mitigate the devastating effects of child malnutrition in the district.